Paying the price? Academic work and parenting during COVID-19 - Protudjer, Jennifer LP; Gruber, Jackie; Mackay, Dylan; Larcombe, Linda (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2022)
Introduction: The shift to remote working/learning to slow transmission of the SARS-CoV-2 virus has had widespread mental health impacts. We aimed to describe how the COVID-19 pandemic impacted the mental health of students and faculty within a health sciences faculty at a central Canadian university.Methods: Via an online survey, we queried mental health in the first four months of the COVID-19 pandemic quantitatively (scale: 1 (most negative)-100 (most positive)) and qualitatively.Results: The sample (n = 110) was predominantly women (faculty 39/59; [66.1%]; students 46/50; [92.0%]). Most faculty were married/common law (50/60; [84.8%]) and had children at home (36/60; [60.0%]); the opposite was true for most students. Faculty and students self-reported comparable mental health (40.47±24.26 and 37.62±26.13; respectively). Amongst women, those with vs. without children at home, reported significantly worse mental health impacts (31.78±23.68 vs. 44.29±27.98; respectively, p = 0.032).Qualitative themes included: “Sharing resources,” “spending money,” “few changes,” for those without children at home; “working at home can be isolating,” including the subtheme, “balancing act”: “working in isolation,” “working more,” for those with children at home.Discussion: Amongst women in academia, including both students and faculty, those with children at home have disproportionately worse mental health than those without children at home.